High entropy spinel oxides and iron-cobalt based electrocatalysts for rechargeable zinc-air batteries - Mongwe, Agnes Monosi (University of the Witwatersrand, Johannesburg, 2024)
The development of effective and stable rechargeable zinc-air batteries (RZABs) using noble-metal free bifunctional electrocatalysts for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) has been a key challenge to its practical applications. This MSc research work strategically investigated some synthetic methods aimed at tuning the physicochemistry and electrochemical properties of two electrocatalysts (i.e., noble-metal free high entropy spinel oxide (HESOx) ((CoCuFeMnNi)3O4) and spinel Fe2CoO4 for rechargeable zinc-air batteries). For HESOx, a simple and reproducible Pechini method was used to synthesize a homogeneous nanosized electrocatalyst HESOx-550. The HESOx-550 was thereafter supported on onion-like carbon (OLC) in (1) an acidic environment to produce HESOx-550/OLCAT (where AT stands for acid-treated) and (2) a nonacidic environment to produce HESOx-550/OLC. The effects of the different synthesis environments on these three samples were thoroughly investigated using different analytical techniques, including X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, thermogravimetric analysis (TGA) and Nitrogen Gas Adsorption analysis. The Nitrogen Gas Adsorption analysis results show that the HESOx-550/OLCAT has the largest surface area and more volume. The electron paramagnetic resonance (EPR) and O1s XPS data consistently proved that HESOx-550/OLCAT has improved oxygen vacancies which are essential in improving conductivity and offering abundant reaction sites. The HESOx-550/OLCAT shows the best bifunctional ORR and OER electrocatalytic performance with a bifunctionality index (ΔE) of 0.70 V in 1 M KOH. In addition, the RZAB air electrode with HESOx 550/OLCAT exhibits high areal capacity (60 mAh cm-2) and areal energy density (73.2 mWh cm-2) with a long-term cycle stability over 112 h in 6.0 M KOH and 0.2 M zinc acetate. The HESOx-550/OLCAT RZAB shows better electrochemical performance than 10wt.% Pt/C- IrO2 when cycled over 315 h under 27% depth of discharge condition. For Fe2CoO4, iron cobalt-based electrocatalysts on Vulcan carbon support were synthesized using a simple reduction method to produce two composites (FeCo-Fe2CoO4/CAnnealed), and (FeCo Fe2CoO4/CMicrowave). The physicochemical analytical methods such as XRD, XPS, Raman, TGA and Nitrogen Gas Adsorption analysis were used to investigate the samples. The electrochemical analysis showed that the FeCo-Fe2CoO4/CAnn had a very low “bifunctionality index” (ΔE) of 0.76 V and the FeCo-Fe2CoO4/CAnn air cathode RZAB demonstrated good stability for over 50 h under harsh DOD conditions (35.2%). The assembled RZABs have areal energy densities of 48.4 mWhcm-2 and 60.5 mWhcm-2 which are higher than the minimum recommended areal energy density of 35 mWhcm-2 (and better than most electrocatalysts reported in the literature). This study has significant contributions to the progress of practical applications of RZABs.
A dissertation submitted in fulfilment of the requirements for the Master of Science degree, to the faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Oxygen reduction reaction (ORR); Oxygen evolution reaction (OER); Rechargeable zinc-air batteries (RZAB); Depth of discharge (DOD); Areal energy density; High entropy spinel oxide (HESO); Bifunctional electrocatalysts; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-13: Climate action